Odpowiedź :
G)5x2 - 10x = 5x2 - 2x - 4
-8x =-4
x= 0,5
H)2x -x2 +x2 -2x +2x -4 =2
2x=6
x=3
-8x =-4
x= 0,5
H)2x -x2 +x2 -2x +2x -4 =2
2x=6
x=3
Cześć!
Szczegółowe wyjaśnienie:
Przykład g)
[tex]5x(x - 2) = x(5x2) - 4 \\ 5x {}^{2} - 10x = 5x {}^{2} - 2x - 4 \\ - 10x = - 2 - 4 \\ 10x + 2x = - 4 \\ - 8x = - 4 \div | - 8 \\ \boxed{x = \frac{1}{2} }[/tex]
Przykład h)
[tex]x(2 - x) + (x + 2)(x - 2) = 2 \\ 2x - x {}^{2} + x {}^{2} - 4 = 2 \\ 2x - 4 = 2 \\ 2x = 2 + 4 \\ 2x = 6 \div | 2 \\ \boxed{x = 3}[/tex]